2019
DOI: 10.1097/md.0000000000015268
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment of multiple tuberculous mycotic aneurysm

Abstract: Rationale:We present a rare case of multiple tuberculous mycotic aneurysm. Multiple aneurysms caused by tuberculosis (TB) are difficult to treat. Here, we discuss a treatment modality using a microcore stent graft.Patient concerns:A 73-year-old man with pain in the back and on the right side of the chest associated with dry cough, presented with an inability to walk since 1-month.Diagnoses:A diagnosis of multiple aneurysms caused by TB was made, based on computed tomography (CT) scan and positive T-spot and Xp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The mean age of the patients was 57 years (range, 6-81 years), with a marked male predominance (13 men, 4 women). The main presenting symptoms were fever (7), chest pain (6), abdominal pain (4), low back pain (2), lower limb pain (2), hemoptysis (1), chest distress and dyspnea (1). Four of them had both chest pain and fever, one of them had both abdominal pain and fever, one of them had both lower limb pain and fever, and only fever was in one case.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean age of the patients was 57 years (range, 6-81 years), with a marked male predominance (13 men, 4 women). The main presenting symptoms were fever (7), chest pain (6), abdominal pain (4), low back pain (2), lower limb pain (2), hemoptysis (1), chest distress and dyspnea (1). Four of them had both chest pain and fever, one of them had both abdominal pain and fever, one of them had both lower limb pain and fever, and only fever was in one case.…”
Section: Resultsmentioning
confidence: 99%
“…TBAA is associated with high mortality due to its high risk of sudden rupture. No patients of TBAA were known to have survived, until the availability of combined technologies of modern imaging, anti-TB therapy and surgical treatment [7]. Early diagnosis and prompt treatment are signi cant for the improvement of survival [8].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a case by Zhao et al [ 42 ] (2019) reported a male patient with chronic obstructive pulmonary disease who was diagnosed with multiple aneurysms. Endovascular repair using a microcore stent graft was performed.…”
Section: Discussionmentioning
confidence: 99%
“…It provides accelerated return to daily routine and early hospital discharge. Early administration of antitubercular treatment has been suggested before endovascular intervention to ameliorate the chances of tuberculosis and aneurysm recurrence 7 8. The patient selection and operative strategy act as critical compounders to patient outcome.…”
Section: Discussionmentioning
confidence: 99%